Presentation: Shepherds, Llamas and Alpacas - Urbano, Henrique Osvaldo (1975)
Allpanchis, with this Pastores, Llamas and Alpacas issue, resumes contact with its subscribers and readers. Economic difficulties and changes in the direction of the IPA have not allowed it to be done in a timely manner. We apologize for this interruption and hope to be able, in the coming months, to publish the numbers corresponding to the years 1976 and 1977.